2003
DOI: 10.4319/lo.2003.48.6.2125
|View full text |Cite
|
Sign up to set email alerts
|

Benthic algae control sediment—water column fluxes of organic and inorganic nitrogen compounds in a temperate lagoon

Abstract: Coastal lagoons are a common land-margin feature worldwide and function as an important filter for nutrients entering from the watershed. The shallow nature of lagoons leads to dominance by benthic autotrophs, which can regulate benthic-pelagic coupling. Here we demonstrate that both microalgae and macroalgae are important in controlling dissolved inorganic as well as organic nitrogen (DIN and DON) fluxes between the sediments and the water column. Fluxes of nitrogen (NH , NO , DON, urea, and dissolved free an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 46 publications
9
104
0
2
Order By: Relevance
“…1). This differs from results of previous core incubation studies in the VCR lagoons that have shown unvegetated sediments were net autotrophic during at least part of the year (McGlathery et al 2001;Tyler et al 2003;Giordano et al 2012), but agrees well with the results found by Hume et al (2011) using the eddy correlation technique (see Fig. 2).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…1). This differs from results of previous core incubation studies in the VCR lagoons that have shown unvegetated sediments were net autotrophic during at least part of the year (McGlathery et al 2001;Tyler et al 2003;Giordano et al 2012), but agrees well with the results found by Hume et al (2011) using the eddy correlation technique (see Fig. 2).…”
Section: Discussionsupporting
confidence: 80%
“…During June 2012, O 2 fluxes were also estimated from sediment core incubations for the bare site (Tyler et al 2003) to compare with the eddy correlation fluxes. Six sediment cores (20 cm deep and 6 cm diameter) with overlying water and seawater from the site were collected and kept on ice in the dark until returned to the lab.…”
Section: Methodsmentioning
confidence: 99%
“…Microphytobenthic biofilms play an important role in estuarine ecosystem functioning, contributing to up to 50% of primary production (MacIntyre et al, 1996;Underwood & Kromkamp, 1999). They constitute an essential food source for grazers Middleburg et al, 2000), regulate the exchange of nutrients across the sediment-water interface (MacIntyre et al, 1996;Tyler et al, 2003) and promote sediment biostabilization (Paterson, 1986;Yallop et al, 1994;de Brouwer et al, 2000;Gerbersdorf et al, 2009;Andersen et al, 2010;Stal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These producers may account for greater than 50% of gross primary productivity, i.e., the total photosynthetic flux, in estuaries (Underwood and Kromkamp 1999). Microphytobenthos have been implicated as a major, and in some cases dominant, controlling factor in estuarine nitrogen cycling (Engelsen et al 2008;Risgaard-Petersen 2003;Tyler et al 2003). Because of their role in moving nitrogen from the overlying water column into the sediments, it is hypothesized that MPB act to buffer estuaries from the effects of eutrophication (McGlathery et al 2004;Meyercordt and Meyer-Reil 1999).…”
mentioning
confidence: 99%